Response of carbon storage to land use change and multi-scenario predictions in Zunyi, China - Yi Liu; Xuemeng Mei; Li Yue; Mingming Zhang (Scientific Reports)
Abstract Evaluating and predicting how carbon storage (CS) is impacted by land use change can enable optimizing of future spatial layouts and coordinate land use and ecosystem services. This paper explores the changes in and driving factors of Zunyi CS from 2000 to 2020, predicts the changes in CS under different development scenarios, and determines the optimal development scenario. Woodland and farmland are the main land use types in Zunyi. Land use change was reflected mainly in the mutual conversion among woodland, farmland, and grassland and by their conversion to construction land and water. In 2000, 2010, and 2020, the CS in Zunyi was 658.77 × 10^6 t, 661.44 × 10^6 t, and 658.35 × 10^6 t, respectively. Woodland, farmland and grassland conversions to construction land and water were primarily responsible for CS loss. The normalized difference vegetation index (NDVI) is the main factor influencing the pattern of CS (q > 10%). Furthermore, the impacts of the human footprint index and population density are increasing. In 2030, the CS of Zunyi is trending downward. Under the ecological-farmland conservation scenario (ECS), the CS is estimated to be 656.67 × 10^6 t, with the smallest decrease (− 0.26%) among timepoints. The effective control of woodland and farmland weakens the trend of CS reduction.